The Hidden Scar - Hei, Muriwai (Te Kaharoa, 2020)
Every line, every curve, every scar there is a hidden message waiting to be discovered and this is my story, how I found a hidden message. Ko Te Miringa tōku ingoa. He uri au nō Te Whānau a Apanui, Te Whakatōhea me Ngāpuhi anō hoki. Do you want to hear something freaky? I’m going to tell you a crazy story of a little scar that changed my life. YES! A fucken scar. Here we go.